The effects of persuasive technology for influencing end-users’ information security awareness - Bawazir, Mohammed Abdullah; Mahmud, Murni; Abdul Molok, Nurul Nuha; Zeki, Akram M. (IIUM Press, 2022)
In today's digital world, information assets have grown in importance, demanding measures to ensure their protection. Ubiquitously, end-users are having trouble ensuring the security of their personal information. The human factor is a major source of vulnerability in the field of information security. Traditional techniques that can be used to influence information security awareness (ISA) remain prohibitively expensive, time-consuming, and repetitive. In light of these challenges, this study proposes persuasive technology to influence end-users' security awareness and behaviour intention. Based on our research, persuasive technology is effective in changing end-users' attitudes and behaviours. In this context, this study assesses the effectiveness of persuasive technology use for influencing end-users' ISA. In addition, this research establishes an integrated model for improving end-users' ISA by incorporating relevant literature and multiple empirically verified theories, including Fogg Behaviour Model (FBM), Protection Motivation Theory (PMT), Theory of Planned Behaviour (TPB), and Technology Acceptance Model (TAM). The integrated model has been proposed based on the main categories of FBM (motivation, ability, and trigger) to identify the effects of key factors in the persuasive technology context for influencing end-user ISA and behaviour intention. The prototype was developed by implementing the persuasive factors of the proposed model to measure the effectiveness of persuasive technology. Quantitative data from an experiment were gathered from 100 participants to validate the proposed research model using the paired sample T-test and partial least squares (PLS) to assess security awareness in the context of persuasive technology. The research findings show that using persuasive technology has a positive influence on ISA. The results also indicate the research model significantly predicts the key factors affecting security awareness and behaviour intention with respect to persuasive technology. Thus, this study suggests a model for the creation and development of a proactive and customised security awareness system. Therefore, persuasive technology, in general, has a positive effect on users' security awareness and the intention of security behaviour.